A study on the strategies to develop pro-social behaviour of preschool children in Sri Lanka - Seneviratne, P. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study aimed at exploring the strategies adopted by preschool teachers in promoting pro-social behavior among preschool children. In this regard the researcher examined the activities conducted by preschool teachers. Four preschool case studies were completed in Homagama Education division. The sample consisted of one preschool under government control, two privately owned preschools and one preschool functioning under a religious organization. Both quantitative and qualitative research techniques were used, including observations. The aim of the observation was to study classroom activities which promoted pro-social behaviors among children. Following pre- planned observation scheme the researcher spent five days in each preschool as an observer. It was revealed that preschool teachers of Sri Lanka take action to promote pro-social behavior among children through their classroom activities through sharing, helping each other, encouraging pro-social behavior and use of collaborative activities. The study recommends that the findings of this research be used by teacher educators and policy makers in the field of preschool education in Sri Lanka.